Ocena procesów konsolidacji w polskim systemie bankowym z perspektywy klientów banku - Konopka, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The article discusses the results of questionnaires administered to 153 respondents from April to June 2010. The purpose of the survey was to gain insight into customer rating of the consolidation processes in the Polish banking industry. Compiled results indicate substantial variance in customer opinions regarding those processes, with multiple pros and cons pointed out. According to the queried customers consolidation objectives were attained mainly through the increase in banking capital, concentration and competitiveness. With regard to the consolidation outcomes respondents rated positively enhanced range of services, better competitiveness and the presence on the internet. Negative consequences were attributed to personnel changes, increased service fees and lack of trust towards foreign investments. Bank customers who took part in the study were of the opinion that the participation of foreign investors had not produced increased stabilization within the Polish banking system.